2008
DOI: 10.2215/cjn.02900707
|View full text |Cite
|
Sign up to set email alerts
|

Viral Infection after Renal Transplantation

Abstract: Viral infections remain a significant cause of morbidity and mortality following renal transplantation. Although cytomegalovirus is the most common opportunistic pathogen seen in transplant recipients, numerous other viruses have also affected outcomes. In some cases, preventive measures such as pretransplant screening, prophylactic antiviral therapy, or post transplant viral monitoring may limit the impact of these infections. Recent advances in laboratory monitoring and antiviral therapy have improved outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
107
1
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 114 publications
(113 citation statements)
references
References 99 publications
3
107
1
2
Order By: Relevance
“…If CMV disease worsens or the viral load increases despite 2 weeks of therapy, ganciclovir resistance should be considered (33). CMV resistance is usually attributed to prolonged exposure to subtherapeutic ganciclovir (especially with oral ganciclovir); however, recently Couzi et al found a higher incidence of drug resistance CMV (UL97 or UL54 mutation) in pre-emptively treated D+R2 kidney transplant recipients, demonstrating that resistance can be seen even in shorter exposures to ganciclovir and its analogues (34).…”
Section: Cytomegalovirus Infectionmentioning
confidence: 99%
See 4 more Smart Citations
“…If CMV disease worsens or the viral load increases despite 2 weeks of therapy, ganciclovir resistance should be considered (33). CMV resistance is usually attributed to prolonged exposure to subtherapeutic ganciclovir (especially with oral ganciclovir); however, recently Couzi et al found a higher incidence of drug resistance CMV (UL97 or UL54 mutation) in pre-emptively treated D+R2 kidney transplant recipients, demonstrating that resistance can be seen even in shorter exposures to ganciclovir and its analogues (34).…”
Section: Cytomegalovirus Infectionmentioning
confidence: 99%
“…Currently there is no consensus regarding the treatment of PTLD, but reduction of immunosuppression is routinely used and can lead to remission in 23%-86% of patients (33). Although antiviral therapy has been used alone or with immunoglobulin, no evidence supports its efficacy (35).…”
Section: Ebv Infection and Ptldmentioning
confidence: 99%
See 3 more Smart Citations